The Centroid of a Lie Triple Algebra - Xiaohong Liu; Liangyun Chen (Abstract and Applied Analysis)
General results on the centroids of Lie triple algebras are developed. Centroids of the tensor product of a Lie triple algebra and a unitary commutative associative algebra are studied. Furthermore, the centroid of the tensor product of a simple Lie triple algebra and a polynomial ring is completely determined.